Museum education and memories production - Farias Júnior, José Petrúcio (2020)
The article discusses the construction of memories built by the visiting public from the museal narrative produced by the Ozildo Albano Museum (Picos / Piauí) and its possible uses for the teaching of history. For this, we will use, on the one hand, the representations about the past conveyed by this cultural institution; on the other hand, we will analyze the perceptions of university students who visited it. From this perspective, we will relate the role of the museum to the scope of cultural memory, through which we emphasize the constitution of 'prosthetic memory', as conceived by Alison Landsberg (2009).